Diving seabirds share foraging space and time within and among species - Masello, Juan F.; Mundry, Roger; Poisbleau, Maud; Demongin, Laurent; Voigt, Christian C.; Wikelski, Martin; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2010)
Ecological theory predicts that animals with similar foraging strategies should not be able to coexist without segregating either in space, time or diet. In communities, intra-specific competition is thought to be more intense than the competition among species, because of the lack of niche partitioning between conspecifics. Hence, while different seabird species can overlap in their foraging distribution, intra-specific competition can drive the neighboring populations of the same species to spatial segregation of foraging areas. To investigate ecological segregation within and among species of diving seabirds, we used a multispecies GPS-tracking approach of seabirds of four species on a small island in the Southwest Atlantic. The present study goes beyond previous work by analyzing simultaneous effects of species and colonies. We observed strikingly strong spatial foraging segregation among birds of the same species, breeding in colonies as close as 2 km from each other. Conspecifics from neighboring colonies used foraging places adjacent to their own colony, and there was little or no overlap with birds from the other colony. A zone with increased predator concentration was completely avoided during foraging trips, likely contributing to the spatial segregation. In addition to spatial segregation, we also observed intra-specific differences in other components of foraging behavior, such as time of day, dive depth and diet. These were most likely caused by optimal foraging of individuals in relation to habitat differences on a local scale, leading to a complex pattern of interactions with environmental covariates, in particular foraging daytime, foraging water layer temperature and depth, distance to coast and bathymetric depth of foraging areas. As mechanisms leading to the spatial segregation we propose a combination of optimal foraging and avoidance of predation.
Keywords: colonial seabirds; diving seabirds; ecological segregation; foraging ecology; Gentoo Penguin, Pygoscelis papua; GPS-temperature-depth loggers; Imperial Shag, Phalacrocorax (atriceps) albiventer; Magellanic Penguin, Spheniscus magellanicus; optimal foraging; Rockhopper Penguin, Eudyptes chrysocome; space segregation; time segregation; ddc:570; ddc:590